Effect of Metal Type on Partial Hydrogenation of Rapeseed Oil‐Derived FAME. (1st June 2013) - Numwong, Natthida; Luengnaruemitchai, Apanee; Chollacoop, Nuwong; Yoshimura, Yuji
Abstract: Supported SiO2 catalysts were studied for the partial hydrogenation of rapeseed oil‐derived fatty acid methyl esters (FAME) for improving its oxidative stability. The effect of metal type: Pt, Pd, and Ni, on catalytic activity and cis – trans selectivity was investigated. Hydrogenation activity was studied in terms of turn over frequency (TOF) of C18:3, C18:2, C18:1, and C18:0 FAME. The highest TOF of C18:3, C18:2, and C18:1 was found for Pd catalyst. However, C18:0 TOF of Pt is higher than that of the Pd catalyst. The higher in C18:0 TOF can explain the low selectivity towards trans ‐monounsaturated FAME of the Pt catalyst, which is due to the subsequent hydrogenation of the intermediate trans ‐monounsaturated to saturated FAME. On the other hand, Ni showed the lowest TOFs when compared with the Pt and Pd catalysts.